Wilhelm Stekel papers - Stekel, Wilhelm, 1868-1940.
Correspondence, articles, biographical sketch, notes on Stekel by his son Eric-Paul Stekel, printed material relating to his son's career as a musician, conductor, and composer, and a photograph of a portrait sketch of Stekel. Correspondents include Heinrich Gomperz, Maximilian Steiner, and George Sylvester Viereck.
Photocopies, in part.
Psychoanalyst.
In German and French.
Forms part of: Sigmund Freud collection.
Keywords: Gomperz, Heinrich, -- 1873-1942 -- Correspondence; Steiner, Maximilian, -- 1874-1942 -- Correspondence; Stekel, Eric-Paul, -- 1898-1978.; Viereck, George Sylvester, -- 1884-1962 -- Correspondence; Psychoanalysis; Psychoanalysts